1976
DOI: 10.1002/app.1976.070200815
|View full text |Cite
|
Sign up to set email alerts
|

Latex–fiber interaction and paper reinforcement

Abstract: SynopsisA model system for studying the reinforcement of paper is provided by the use of cationic latexes. The control of pH during addition of the latex to the pulp determines the uniformity of the latex deposition on the fibers. It is demonstrated, using scanning electron microscopy and mechanical testing of the sheet, that the dry and wet strength properties are improved by the more uniform distribution of a film-forming latex. Conversely, a nonfilming latex impedes bonding to the extent that the fiber surf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

1979
1979
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…34,35 Latex nanoparticles are highly interesting for cellulose modification as the modification can be conducted in allaqueous conditions and the technique is already well-established in industry. Latex nanoparticles ( poly(styrene-co-butadiene)) have been shown to, for example, enhance the tensile strength of paper sheets, as investigated by Alince et al 36,37 Additionally, composites composed of cellulose adsorbed with elastomeric core-shell latex particles of poly(n-butyl acrylateco-methyl methacrylate/2-ethylhexylacrylate-co-styrene) exhibited improved mechanical properties, increasing both impact and tensile strengths. 38 Inspired by the above studies, we previously reported the synthesis of cationic latex nanoparticles by RAFT-mediated emulsion polymerization, utilizing a PDMAEMA-based macroRAFT, for the polymerization of MMA.…”
Section: Introductionmentioning
confidence: 99%
“…34,35 Latex nanoparticles are highly interesting for cellulose modification as the modification can be conducted in allaqueous conditions and the technique is already well-established in industry. Latex nanoparticles ( poly(styrene-co-butadiene)) have been shown to, for example, enhance the tensile strength of paper sheets, as investigated by Alince et al 36,37 Additionally, composites composed of cellulose adsorbed with elastomeric core-shell latex particles of poly(n-butyl acrylateco-methyl methacrylate/2-ethylhexylacrylate-co-styrene) exhibited improved mechanical properties, increasing both impact and tensile strengths. 38 Inspired by the above studies, we previously reported the synthesis of cationic latex nanoparticles by RAFT-mediated emulsion polymerization, utilizing a PDMAEMA-based macroRAFT, for the polymerization of MMA.…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8] Furthermore, this procedure may possibly be integrated and performed in conventional processes, for example in paper making. Alince et al [9][10][11] reported already in 1976 the favorable effect of addition of a poly(styrene-co-butadiene) latex for paper reinforcement. The same copolymer composition was employed to prepare nanocomposite films by casting latex dispersion with cellulose whiskers which considerably improved the mechanical properties.…”
Section: Introductionmentioning
confidence: 99%
“…[71] The synthesis of the latex particles was performed by emulsion polymerization utilizing hydrogen peroxide and ferric nitrate as initiator to yield latexes composed of copolymers of PDEAEMA-co-PS-co-PB. They used the latexes to study the effects of the deposition and distribution of latexes on cellulose fiber surfaces at different pH and amount of latex added.…”
Section: Cationic Latex Particlesmentioning
confidence: 99%